THE IMPACT OF WORDWALL ONLINE GAMES ON ENGLISH VOCABULARY MASTERY IN READING - Al Firdaus, M. Wildan Maulana; Rahmawati, Eva (Universitas Muhammadiyah Metro, 2024)
This quantitative quasi-experimental study examines vocabulary mastery differences between students taught with Wordwall Online Games and students taught with traditional learning methods. Conducted with 58 junior high school 8th graders, participants were divided into control and experimental groups. Vocabulary proficiency was assessed via an updated vocabulary level test administered through Google Forms, with data analyzed using paired sample t-tests. Findings indicate significant vocabulary improvement in both groups from pre- to post-test. Effect size calculations using Cohen's d revealed large effect values for both groups, with Cohen's d = 2.19718 for the experimental group. Cohen's d = 1.52645 for the control group, reflecting a difference of 0.67073. Despite both methods being practical, this difference suggests a notably stronger impact of Wordwall Online Games on vocabulary mastery than traditional media. Thus, while Wordwall enhances vocabulary acquisition more substantially, traditional media also plays a valuable role in vocabulary development, supporting its continued use in language education. This research could enhance vocabulary mastery in students' reading skills, encourage interactive teaching methods, and serve as a valuable resource for future studies on using Wordwall Online Games to improve vocabulary in junior high school.